Autotransplantation: An alternative treatment for horizontally impacted permanent incisors: A case report with review of literature - Ritesh R Kalaskar; Priyanka Bhaje; Ashita Ritesh Kalaskar; Priyanka Sharma (Wolters Kluwer Medknow Publications, 2020)
Horizontally impacted permanent maxillary incisors are rarely treated by surgical extraction due to their unfavorable position and traumatic extraction. Fixed prostheses such as fixed partial dentures and implants are contraindicated in children because of their growing age, as they adversely affect bone growth. In this case report, we have presented 18-month follow-up study of a 13-year-old child with a horizontally impacted permanent maxillary lateral incisor which was autotransplanted into its original position. To avoid interference in periodontal healing, intentional endodontic treatment was carried out followed by placement of a jacket crown.